Graphene films printable on flexible substrates for sensor applications. (16th December 2016) - Banerjee, Indrani; Faris, Tsegie; Stoeva, Zlatka; Harris, Paul G; Chen, J; Sharma, Ashwani K; Ray, Asim K
Abstract: Fifteen-layered graphene films have been successfully deposited onto flexible substrates using a commercial ink consisting of graphene particles dispersed in an acrylic polymer binder. A value of 74.9 × 10 5 cm − 2 was obtained for the density of defects, primarily located at the flake edges, from the ratio of the D and G Raman peaks located at 1345 cm − 1 and 1575 cm − 1 respectively. 0.5 μ m thick drop-cast films on interdigitated silver electrodes exhibited Ohmic conduction with a small activation energy of 12 meV over the temperature range from 260 to 330 K . The photo-thermoelectric effect is believed to be responsible for photoconduction through graphene films under illumination intensity of 10 mW m −2 at 270 nm, corresponding to the UV absorption peak. The photo-transient decay at the bias of 1 V involves two relaxation processes when the illumination is switched off and values of 8.9 × 10 3 and 4.3 × 10 4 s are found for the relaxation time constant using the Kohlrauch stretched exponential function analysis.